Innovation In Perspective Product Service to Create International Achievement Culture - Sri Lestari; Titi Prihatin; Haryono Haryono (International Conference on Science, Education, and Technology, 2023)
Innovation education in something agency own a very vital role that deserves given attention more for maximizing potential student become an achievement. So far, innovation education much concerned with matters of pedagogy, technology, or rules in the organization. Purpose of this article to see educational innovation from the perspective of co-produced services and joint interactions in order to improve student achievement. Service innovation solution important in seeing the other side of innovation, which can influence the formation of student character and achievement culture. This research used a case study qualitative approach at SD Hj Isriati Baiturrahman 1 Semarang. The results showed that the service innovations provided included teaching and achievement development patterns, student interactions, teacher-to-teacher relationships, parental interactions, after-school (extracurricular) activities, school appreciation, co-production with the education office and related companies. Service innovations produced with multi-agents have been able to improve the achievements to international level in the last 3 years. Managerial and policy implications in achieving student achievement can be guided by using the principle of service-friendly innovation.